Effective venture capital market development concept - Anita Matisone; Natalja Lace (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
This paper presents the results of the study on the venture capital (VC) market development drivers in small countries with underdeveloped VC markets. Based on the literature content analysis, the authors developed a comprehensive list of factors influencing VC market status. The relevance of the factors in countries with small, underdeveloped VC markets was studied between experts involved in shaping Latvian VC market. The study revealed that all factors (in total 73) delivered from the literature influence the VC market in the countries such as Latvia. Sixty-three factors have an impact above moderate, and providing public funding for VC funds is only one of the factors. The results highlight the importance of the shift from the typical public support approach of providing VC managers with funding to the government involvement in also shaping other conditions necessary for VC market self-sufficiency development. Based on the study, the authors propose a conceptual model for further public support design. The model has three dimensions of meta factor groups (VC market participants, environment, embedded characteristics). It is necessary to evaluate and, if possible, provide public support in each of the meta-factors' groups. The authors propose to use the model and the list of impactful factors as tools for further governmental support for VC.
Keywords: 650; conceptual model; public interventions; venture capital